Effect of Biochar on Growth of Main Nursery Palm Oil Seedlings (Elaeis guineensis Jacq.) on Soil Chemical Properties in Vertisol Soil Planting Media - Lubis, Erwin Junaidi (Akademi Komunitas Perkebunan Yogyakarta, 2025)
Plant growth response of palm oil seedlings (Elaeis guineensis Jacq.) on D x P Yangambi varieties using biochar applications made from palm oil shells, rice husks, and corn cobs in the Main Nursery. This study aims to determine the effect of the application of several types of biochar on the growth of palm oil seedlings (main nursery) on soil chemical properties namely C-Organic, N-Total, Phosphorus Nutrients, Potassium Nutrients and Soil pH in Vertisol Soil Planting Media. This research was conducted at the Soil Laboratory Practice Farm of the Indonesian Institute of Palm Technology, Medan, North Sumatera. The research used Factorial Randomised Group Design (RGD) with 3 replications. The research was conducted for 4 months. The results showed a significant effect on the application of rice husk biochar, palm oil shells and palm oil cobs and the application of N.P.K.Mg 15.15.6.4 fertilizer at a fertilizer dose of 7.5 g.polybag-1 on the parameters of plant height, stem circumference, number of leaf midribs, and biochar treatment can increase soil pH, Phosphorus nutrients, and Potassium nutrients.